Implementasi Penilaian Autentik pada Mata Pelajaran Al-Qur’an Hadits di MAN 1 Tapanuli Tengah - Rudya Ismail; Erawadi Erawadi; Zulhammi Zulhammi (ISLAMIKA, 2023)
The background of this research is that there are still teachers of Al-Qur'an-Hadith who judge it only as a formality, assess students only modestly. In fact, when referring to the 2013 curriculum assessment, there are many types of authentic assessment, including: authentic assessment of affective aspects, assessment of cognitive aspects, assessment of psychomotor aspects. So that researchers are interested in studying the assessment of authentic Al-Qur'an Hadith teachers at MAN 1 Tapanuli Tengah, Barus District, Central Tapanuli Regency. This study uses a qualitative phenomenological approach and a descriptive research type. Descriptive data is data obtained in the form of words which are then attempted to be described and interpreted. Data collection techniques using unstructured interviews, participant observation and documentation. Data analysis uses data reduction procedures, data presentation and conclusion or verification. The research results show that; First, an authentic assessment of affective (spiritual and social) aspects used at MAN 1 Tapanuli with observation, interview and documentation techniques. Second, the authentic assessment of cognitive aspects (knowledge) used at MAN 1 Tapanuli Tengah uses written test techniques and oral tests. This is illustrated for written test techniques used to evaluate students by carrying out daily tests while oral tests are used at the beginning and at the end of learning, if at the beginning of learning to perceive last week's lesson, at the end of learning to solidify learning. Third, the authentic assessment of psychomotor aspects (skills) used at MAN 1 Tapanuli Tengah is in accordance with the Minister of Education and Culture in its application, Al-Qur'an-Hadis teachers use practical techniques, projects and portfolios.